2020
DOI: 10.30534/ijatcse/2020/37932020
|View full text |Cite
|
Sign up to set email alerts
|

Analysis Loyalty in Video Conference Application Zoom on COVID 19 Quarantine in Jakarta

Abstract: The effect of the coronavirus outbreak towards Jakarta residents is an enactment of large-scale social restrictions regulation to prevent virus transmission. Work from home also causing an increase in video conference user data traffic. Zoom application is experiencing the number of users increase throughout March 2020. Even so, some people start doubting the Zoom user data security. Therefore, the question in this research is how trust impacts on video conference application user loyalty in Jakarta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Zoom allow up to 100 people at a time) [7]. More than 90.000 education institution around the world used Zoom to perform teaching-learning and Zoom application is becoming more popular among student and teacher to hold video conference and webinar even privacy risk is appear [8]. So that, e-learning is becoming more important to keep learning process running well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zoom allow up to 100 people at a time) [7]. More than 90.000 education institution around the world used Zoom to perform teaching-learning and Zoom application is becoming more popular among student and teacher to hold video conference and webinar even privacy risk is appear [8]. So that, e-learning is becoming more important to keep learning process running well.…”
Section: Introductionmentioning
confidence: 99%
“…The next results in the student questionnaire analysis found that the way the teacher taught still used conventional methods not to match students' characteristics (learning styles) [17].E-learning failure is reporting appear when the instruction cannot match with the student expectation [18]. Despite the online environment having a strong relationship with learning behavior [8], teaching style adaptation with each student's learning styles will enhance distance education [19]. The learning style can be used by a teacher to convey material content for students [11].Learning style is considering a valid predictor of success in a Web-based learningenvironment [19].…”
Section: Introductionmentioning
confidence: 99%
“…Early June 2020, WHO issued a recommendation for all people to use masks, healthy and sick people [3]. Even though big cities have implemented much work from home [4] [5] [6], there is still a large proportion of workers who have to work from the office. It causes the need for public transportation to remain a priority for most workers.…”
Section: Introductionmentioning
confidence: 99%